2013
DOI: 10.1108/03090561311324264
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of need for cognition on drivers of customer loyalty

Abstract: Purpose -While satisfaction, value, image, and credibility are commonly assumed to drive customer loyalty, there is nevertheless reason to question whether their effects vary across groups of consumers. This paper seeks to explore how individuals with contrasting need-for-cognition (NFC) levels differ in using memory-based information when forming behavioral intentions towards a current service provider. Design/methodology/approach -The authors tested the hypotheses by means of survey data from customers of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 66 publications
1
24
0
1
Order By: Relevance
“…For instance, Walsh et al (2008) tested the moderating effects of several demographic variables (age, gender, income) on the satisfaction-loyalty link; results indicated that only income influenced the strength of the relationship. In studies reviewed by Hansen et al (2013), the majority indicate that demographics offered fewer explanations compared to psychological factors as moderators on the effects of loyalty antecedents to loyalty. On using need for cognition as a moderator on the satisfaction-loyalty relationship, Hansen et al (2013) noted that the variable significantly moderates the relationship.…”
Section: H2mentioning
confidence: 94%
See 3 more Smart Citations
“…For instance, Walsh et al (2008) tested the moderating effects of several demographic variables (age, gender, income) on the satisfaction-loyalty link; results indicated that only income influenced the strength of the relationship. In studies reviewed by Hansen et al (2013), the majority indicate that demographics offered fewer explanations compared to psychological factors as moderators on the effects of loyalty antecedents to loyalty. On using need for cognition as a moderator on the satisfaction-loyalty relationship, Hansen et al (2013) noted that the variable significantly moderates the relationship.…”
Section: H2mentioning
confidence: 94%
“…Few studies (e.g. Gountas and Gountas, 2007;Han and Ryu, 2009;Hansen et al, 2013) have considered either the environmental or personal factor to be an antecedent of loyalty through mediators like consumption emotions, cognition, and satisfaction. Such an approach appears to provide a limited understanding of consumer loyalty which have been noted to be influenced by environmental factors (Han and Ryu, 2009) as well as personal factors (Bove and Mitzifiris, 2007;Lin, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive image represents an asset to the service provider, and customers often trust that the provider will not jeopardize this by decreasing its service standard level [29]. Customers nowadays are reluctant to compromise on service standard, and therefore service standard has turn out to be the key to customer acknowledgement.…”
Section: Literature Reviewmentioning
confidence: 99%